The dual impact of physical exercise on depression and fall risk in older Chinese adults — evidence from CHARLS 2020 - Yuan, Wenhui; Cui, Jinghang (Frontiers in Public Health, 2025)
IntroductionRapid population aging in China has elevated concerns regarding the mental and physical well-being of older adults. This study investigates the interrelationships among physical exercise, depression, and fall risk using data from the 2020 wave of the China Health and Retirement Longitudinal Study (CHARLS).MethodsWe analyzed a sample of 3,694 older adults. An ordinary least squares regression model was employed to assess the impact of physical exercise on depression, while a logistic regression model was used to examine the effect on fall risk. Key control variables included age, biological sex, income, marital status, and major accident history. Mediation analyses were then conducted to test the indirect effect of exercise on fall risk through depression, with subgroup analyses comparing urban and rural respondents.ResultsResults from the depression model revealed that physical exercise significantly reduced depression scores (β=−0.3156;p=0.002), and males exhibited lower scores relative to females. The falls model indicated a trend toward reduced fall risk with increased exercise (β=−0.0738;OR≈0.929;p=0.061), while older age and female gender are associated with elevated risk. Mediation analysis demonstrated a significant indirect effect in the urban group (mean indirect effect = −0.0338), but not in the rural group (mean indirect effect = −0.0056).DiscussionThese findings suggest that physical exercise not only directly improves mental health but also indirectly reduces fall risk through alleviating depressive symptoms in urban older adults. The lack of a significant mediating effect in rural areas suggests that local contextual factors may alter the exercise-depression-fall pathway. The results support integrated public health interventions tailored to local settings to enhance both mental and physical outcomes among China’s aging population.